(untitled) (Historia, 2021)
In the Foreword to Andrew Duminy and Bill Guest’s Natal and Zululand: From Earliest Times to 1910, published in 1989, the late Professor Colin Webb remarked, with approbation, that exploration of Natal’s past continued vigorously. Graham Dominy’s thorough account of the role of the garrison at Fort Napier exemplifies and embellishes that practice. At the outset he makes a significant observation about the strength of the garrison which has great relevance to the frugal way the British maintained their empire: “The power of the garrison was less than it sought to portray, but it was a token of the greater power of the empire, which could be brought into play if locally challenged” (p xvi). As such, the garrison symbolised British hegemony and promoted a sense of security amongst the small settler population. But as Dominy also notes, “the garrison masked the weaknesses of the state through military pageantry and marched out on minor expeditions in response to panic and rumours of invasion” (p 58). Although he does not make this point, the extent to which settlers were consistently aware of their vulnerability was their involvement in the rifle associations. No other civic organisation was as prolific. Initiated by Ordinance 11 of 1855, by 1904 there were 62 Volunteer Corps or rifle associations, as they were then called.1